2021
DOI: 10.31920/2634-3622/2021/v10n1a6
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Gender-Based Violence against Women in South Africa : A Call for Action

Abstract: The prevalence of gender-based violence in South Africa is an intense and widespread problem that impacts almost every aspect of life. This call for states’ intervention in the prevention of gender-based violence (GBV) in the country. Reports show that intimate partner violence and sexual coercion are the most common forms of GBV globally, and these are the types of violence that are explored in this paper. GBV has serious consequences for women’s health, such as homicides, suicides, AIDS-related deaths as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 6 publications
0
21
0
1
Order By: Relevance
“…South Africa is one of the countries with the highest statistics of gender-based violence crimes in the world (Enaifoghe et al, 2021). Moreover, some of these crimes go unreported (Nobanda et al, 2021).…”
Section: Figure 2 Promoting Moral Valuesmentioning
confidence: 99%
“…South Africa is one of the countries with the highest statistics of gender-based violence crimes in the world (Enaifoghe et al, 2021). Moreover, some of these crimes go unreported (Nobanda et al, 2021).…”
Section: Figure 2 Promoting Moral Valuesmentioning
confidence: 99%
“…The Centre for the Study of Violence and Reconciliation (CSVR) reported that experiencing violence as a child or growing up in a household that uses violence as a means of communication contributes towards violence becoming normalised for the individual in later life (CSVR, 2016). Such victims are often subjected to physical assault leading to bodily harm, contracting HIV/AIDS, sexually transmitted diseases and the possibility of unwanted pregnancies leading to unsafe abortions (Enaifoghe et al, 2021). The trauma of GBV translates into psychological health instability such as depression, fear, anxiety, low self-esteem, mental illness and suicidal thoughts or action and in extreme cases, femicide (Weil, 2016).…”
Section: Childhood Experience and Traumamentioning
confidence: 99%
“…The trauma of GBV translates into instabilities of psychological health such as depression, fear, anxiety, low self-esteem, mental illness and suicidal thoughts or action and in extreme cases, femicide (Weil, 2016). Additionally, the victim will suffer from a change in socioeconomic perspective in the form of stigmatisation, rejection, isolation and decreased earnings leading to increased poverty (Enaifoghe et al, 2021).…”
Section: Childhood Experience and Traumamentioning
confidence: 99%
See 1 more Smart Citation
“…La violencia basada en el género (VBG) es un problema social de gran magnitud que afecta los derechos de las mujeres a nivel mundial (Enaifoghe et al, 2021). Las estadísticas revelan que un número alarmante de mujeres ha experimentado violencia física o sexual, y que muchas de ellas no denuncian estos actos debido al temor a sus agresores o a la vergüenza social.…”
Section: Introductionunclassified